الرصد الحيوي لتلوث الهواء ببعض المعادن الثقيلة المحمولة بغبار المقالع باستخدام أوراق الصنوبر البروتي(Pinus brutia Ten.) كمؤشر حيوي، حالة موقع تحريج كفردبيل- جبلة - شاطر زهير; علي وائل; نيصافي إبراهيم; صالح لانا (Latakia University Journal -Biological Sciences Series, 2017)
هدفت هذه الدراسة إلى تقدير مستوى التلوث الجوي ببعض المعادن الثقيلة المحمولة بغبار المقالع المجاورة لموقع تحريج كفردبيل باستخدام أوراق الصنوبر البروتي كمؤشر حيوي. جُمعت عينات الغبار والأوراق أواخر شهر تموز من العام 2016، وقُدرت كميات الرصاص والنيكل والزنك باستخدام جهاز التحليل الطيفي بالامتصاص الذري بـ ppm على أساس الوزن الجاف للعينة. بلغت قيم المعادن المتراكمة في الأوراق كمتوسط كما يلي: (Pb= 45.57 ppm, Zn= 13.64 ppm, Ni= 7.64 ppm )، بينما كانت قيمها في غبار المصائد كالآتي (Pb= 66.1 ppm, Zn= 15.8 ppm, Ni= 19.6 ppm). بينت النتائج تلوث الموقع المدروس بالرصاص والنيكل أما الزنك فكان ضمن الحدود الطبيعية، ووجدت علاقة ارتباط قوية بين متوسط كمياتها في أوراق الصنوبر البروتي مع كمياتها في الغبار المتراكم في المصائد (r= 0.98)، كما فسَّرت معادلات الانحدار التباينات في تراكم المعادن المدروسة بالنسبة للغبار المتراكم على الأوراق كما يلي: 40% رصاص، 40% زنك و 20% نيكل. بالنتيجة يمكن اعتماد أوراق الصنوبر البروتي في الموقع المدروس كمؤشر حيوي لتلوث الهواء بالرصاص والزنك والنيكل. This study aimed to estimate the level of air pollution in some portable heavy metals in dust quarries by needles of Pinus brutia Ten. as biomonitor In site of Kfardabeel Stand- Jableh. The samples of dust and leaves were collected at the end of July in 2016, Atomic absorption spectrophotometer was used to determine the amounts of Lead, Zinc, Nickel (ppm, dry weight). The average of accumulated metals in the needles were estimated: (Pb= 45.57 ppm, Zn= 13.64 ppm, Ni= 7.64 ppm), while their amounts in the dust were done as following: (Pb= 66.1 ppm, Zn= 15.8 ppm, Ni= 19.6 ppm). The results showed that the studied site is polluted with Pb and Ni whereas Zn is in the natural range. a strong correlation between heavy metals amounts in the needles and their amounts in the trapped dust (r= 0.98) was detected, also regression equations have explained the variations in accumulation of studied metals in relation to the accumulated dust on needles as following: 40% Pb, 40% Zn, 20% Ni. Consequently results confirmed the possibility of detecting the atmospheric Pb, Zn, Ni pollution in the studied site using P. brutia Needles as a biomonitor.